2023
DOI: 10.1002/adma.202211612
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Induced Mott‐Insulator‐to‐Metal Phase Transition in Ultrathin Intermediate‐Spin Ferromagnetic Perovskite Ruthenates

Abstract: Light control of emergent quantum phenomena is a widely used external stimulus for quantum materials. Generally, perovskite strontium ruthenate SrRuO3 has an itinerant ferromagnetism with a low‐spin state. However, the phase of intermediate‐spin (IS) ferromagnetic metallic state has never been seen. Here, by means of UV‐light irradiation, a photocarrier‐doping‐induced Mott‐insulator‐to‐metal phase transition is shown in a few atomic layers of perovskite IS ferromagnetic SrRuO3−δ. This new metastable IS metalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“… Therefore, the in situ oxygen annealing enhances the domain I-dominated Hall signal, forming a considerable competition of two domains (domain I and domain II) as well as the appearance of a hump-like anomalous Hall signal. Similar oxygen vacancy-induced two domains, which can be reversibly manipulated by the external electric field and light illumination, has been observed in the previous studies. , Therefore, we claim that the hump-like AHE is mainly related to the oxygen vacancy and strain-modulated domain I and domain II, which is closely bonded to the nontrivial band structure of SRO.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“… Therefore, the in situ oxygen annealing enhances the domain I-dominated Hall signal, forming a considerable competition of two domains (domain I and domain II) as well as the appearance of a hump-like anomalous Hall signal. Similar oxygen vacancy-induced two domains, which can be reversibly manipulated by the external electric field and light illumination, has been observed in the previous studies. , Therefore, we claim that the hump-like AHE is mainly related to the oxygen vacancy and strain-modulated domain I and domain II, which is closely bonded to the nontrivial band structure of SRO.…”
Section: Resultssupporting
confidence: 85%
“…Similar oxygen vacancy-induced two domains, which can be reversibly manipulated by the external electric field and light illumination, has been observed in the previous studies. 65,66 Therefore, we claim that the hump-like AHE is mainly related to the oxygen vacancy and strain-modulated domain I and domain II, which is closely bonded to the nontrivial band structure of SRO.…”
Section: Anomalous Hall Effect Of Freestanding Sro Filmsmentioning
confidence: 88%
“…Liu et al, found that ultraviolet (UV) light exposure can initiate a reversible transition from a Mott insulator to a metallic state in a few atomic layers of intermediate-spin (IS) ferromagnetic strontium ruthenate (SrRuO 3−δ ), as shown in Figure d and Figure e. The process involves photocarrier doping, which suggests that light stimulation can be used to achieve room-temperature ferromagnetism and potentially other quantum phases, like unconventional superconductivity .…”
Section: Light Modulation Of Magnetismmentioning
confidence: 99%
“…In the condensed matter system, various types of DOF, including spin, lattice electron, and orbital, interact and compete (Figure 4a), which consequently results in the Mott insulator being susceptible to external stimuli. Among various functionalities in the strongly correlated oxides (Figure 4b), the MIT behaviors are triggered by external perturbations such as light, [55,56] electric field, [57][58][59] temperature, [60,61] and lattice strain (Figure 4c). [62,63] It means that Mott insulators can exhibit MIT behaviors in response to various types of external stimuli, making them applicable in diverse and multifunctional nanoelectronics.…”
Section: Origin Of Mitmentioning
confidence: 99%